HYDROGEOCHEMICAL INVESTIGATION OF SURFACE AND GROUNDWATER QUALITY OF PAGO, NORTH CENTRAL NIGERIA - Musa, Aisha; Tsado, F.; Amadi, A. N.; Aweda, A. K.; Habib, I. A.; Abdulkadir, H. (FUDMA Journal of Sciences, 2024)
This study investigated the hydrogeochemical characteristics of surface and groundwater in Pago, North Central Nigeria, a region characterized by Precambian Basement Complex rocks. Water samples collected from wells and streams were analysed using Atomic Absorption Spectrometer (AAS) to analyse for major ions and heavy metals in the water samples. The water quality of the study region was evaluated using hydrogeochemical indices. The hydrogechemical analysis shows that most of the analysed parameters fell within WHO permissible limits, elevated COD levels in some samples indicate potential organic pollution, which may pose risks to human health and aquatic ecosystems. The CF shows low concentrations (1) of COD. The values of PLI were generally low, indicating minimal pollution. The WQI showed samples with excellent (
Keywords: Quality investigation; Surface and Groundwater; Pollution Indices; North central Nigeria